Comparison of penetrating needles and non-penetrating needles with electrical stimulation combined with exercise training for relieving dyspnea and improving exercise tolerance in chronic obstructive pulmonary disease patients: A single-blind randomized controlled trial - Ying He; Gui-yuan Li; Chun-zhi Tang; Li-ming Lu; Guang-yi Xiong; Yi Gao; Juan Tong; Guang-en Zhong (Integrative Medicine Research)
Background: Chronic obstructive pulmonary disease (COPD) is characterized by persistent airflow limitation. The purpose of this study was to evaluate the effectiveness of the use of penetrating needles with electrical stimulation combined with exercise training for relieving dyspnea and improving exercise tolerance among COPD patients. Methods: A total of 85 patients were recruited and randomly assigned to receive treatment with either penetrating needles with electrical stimulation (PE) or non-penetrating needles with electrical stimulation (NPE) 3 times a week for 8 weeks, thereby resulting in a total of 24 treatments. Both groups underwent exercise training. The evaluations were conducted at baseline, after 14 treatments, and after 24 treatments. Results: The PE group showed significant improvement in the 6-minute walk distance (6MWD) after the 14th treatment. For the pulmonary function test, percentage of maximal voluntary ventilation (MVV%), maximal expiratory flow (MEF) after 75% of the forced vital capacity (FVC), MEF after 50% of FVC, and MEF after 25% of FVC were improved in the PE group, and especially MVV% was significantly greater than that in the NPE group. For cardiopulmonary exercise testing, percentage of oxygen consumption per kg body weight (VO2/kg), percentage of ventilation volume per minute (VE), maximal ventilation volume per minute (VEmax), ventilatory equivalent for oxygen (VE/VO2), and ventilatory equivalent for carbon dioxide (VE/VCO2) were significantly higher than the NPE group. The scores of COPD assessment test in the PE group significantly improved. Conclusion: Treatment with penetrating needles with electrical stimulation combined with exercise training may be clinically useful for COPD patients in relieving dyspnea and improving exercise tolerance. Trial Registration: Chinese Clinical Trial Registry, ChiCTR1900028627.